Limiting Reactants in Chemical Analysis: Influences of Metals and Ligands on Calibration Curves and Formation Constants for Selected Iron-Ligand Chelates - Stauffer, Mark T.; Weller, William E.; Kubas, Kimberly R.; Casoni, Kelly A. (IntechOpen, 2012)
None